Predictors of uncontrolled hypertension among patients receiving treatment from public primary care clinics in Pulau Pinang, Malaysia - Tan, Hooi Shyuan; Ariffin, Ahmad Azuhairi; Mohd Zulkefli, Nor Afiah; Mustapha, Feisul Idzwan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Hypertension treatment aims to reduce morbidity and mortality from cardiovascular and renal complications. In Malaysia, there is a high prevalence of uncontrolled hypertension among patients on treatment. This study aimed to identify the predictors of uncontrolled hypertension among patients receiving treatment from public primary care clinics in Pulau Pinang, Malaysia. Methods: An unmatched case-control study with 1:1 ratio was conducted among 334 hypertensive patients receiving treatment from selected public primary care clinics. Mean blood pressure measurements from the last two clinical visits were used to determine the hypertension status, and uncontrolled hypertension was defined as 140/90 mm Hg or higher. The cases were those with uncontrolled hypertension, while the controls were those with controlled hypertension. Participants were recruited by simple random sampling. Independent variables were sociodemographic factors, clinical and psychosocial factors, medication adherence, lifestyle modification, and clinical inertia. Data were collected using validated questionnaires and review of medical records. Multiple logistic regression analysis was performed by using IBM SPSS Statistics 25. Results: The mean age of respondents was 59 years (SD=11). Patients with medication non-adherence had 11.36 times higher odds of uncontrolled hypertension (aOR=11.36, 95% CI=6.59, 19.56, p <0.001). Clinical inertia increased 7.82 times the odds of uncontrolled hypertension (aOR=7.82, 95% CI=2.65, 23.09, p<0.001). Conclusion: Addressing medication adherence and clinical inertia are vital in reducing uncontrolled hypertension. The findings would help to prioritise interventions to improve the clinical management of hypertension and patient outcomes.